If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3y-3.5=9y-3.5
We move all terms to the left:
3y-3.5-(9y-3.5)=0
We get rid of parentheses
3y-9y+3.5-3.5=0
We add all the numbers together, and all the variables
-6y=0
y=0/-6
y=0
| 0,5t+1=2t+1,5 | | 5+1,5t=3+2,5t | | 30+6p=7(p+6)–5 | | 4x+60x=30 | | 4x+60=x | | 4-4/(2x-1)-9=-5 | | 0=96-16x^2 | | 5a^2=9a=4+0 | | 0.55*x=100 | | 3(x+5)=5x-31 | | 4(5x-2)=2)(9x+3) | | 100/n=124 | | 50=5(x=5) | | a^2+9a+4=0 | | 9x-8=2x+11 | | 20+x+8x=60 | | x-3/4=1,1/2 | | g4=3.2 | | 2.5^x=1/6 | | 8x+42=x54 | | 7x+-2=-54 | | 3n-2=5n=12 | | 120/111=240/x | | 2(3x=1)=17 | | 4e+6-11e=-50 | | x2-3x+40=0 | | 7x+14=700 | | 36=6x+9 | | x2+2x=-10 | | 16^x=320 | | 6n+4/2n=5 | | 7a+1=-4-a |